Crises and the Distribution - Koulovatianos, Christos (Journal of Income Distribution®, 2016)
An economic crisis can be described as a rapid development of events manifested by sudden misallocation of resources. High percentages of bankrupt companies or financial institutions, low investment and unusually high unemployment are some examples of misallocation. In a state of resource misallocation, economic efficiency is compromised. The real economy’s fundamental ingredients, such as productive potential being one, thereby lose connection to economic outcomes. It is reasonable to think that such misallocation can be detected in the income and wealth distribution. This conjecture and approach is a key motivation behind this special volume. At the same time, whether it be a financial crisis (a stock market crash, the bursting of any financial “bubble”), a banking crisis, a currency crisis, or a sovereign default, some signs of misallocation before the crisis may be detectable in the income/wealth distribution through slower processes that have possibly started years before a crisis. This second conjecture is another key motivation behind initiating this special volume.